New Strategy for the Synthesis of Telmisartan: An Antihypertensive Drug - Venugopal, S.; Ramanatham, J.; Devanna, N.; Sanjeev Kumar, A.; Ghosh, Samir; Soundararajan, R.; Kale, Bhima; Mehta, G.N. (Asian Journal of Chemistry, 2010)
An improved, convergent and industrially useful process suitable for large-scale production of telmisartan has been described. The key steps are Suzuki coupling for the preparation of key intermediate 4,4-dimethyl-2-(4'-methanesulfonyloxy methylbiphenyl-2-yl)oxazoline of telmisartan, N-alkylation and oxazoline hydrolysis.